Reliability and Security Analysis on Two-Cell Dynamic Redundant System - Hongsheng Su (Institute of Advanced Engineering and Science, 2013)
Based on analysis on reliability and security on three types of two-cell dynamic redundant systems which has been widely applied in modern railway signal system, whose isomorphic Markov model was established in this paper. During modeling several important factors, including common-cause failure, coverage of diagnostic systems, online maintainability, and periodic inspection maintenance, and as well as many failure modes, were considered, which made the established model more credible. Through analysis and calculation on reliability and security indexes of the three types of two-module dynamic redundant structures, the paper acquires a significant conclusion, i.e., the safety and reliability of the kind of structure possesses an upper limit, and can not be inordinately improved through the hardware and software comparison methods under the failure and repairing rate fixed. Finally, the paper performs the simulation investigations, and compares the calculation results of the three redundant systems, and analysis each advantages and disadvantages, and gives out each application scope, which provides a theoretical technical support for the railway signal equipments selection. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2492